Assessing the evolution of scientific publications in orthopedics journals from mainland China, Hong Kong, and Taiwan: a 12-year survey of the literature. Issue 1 (December 2016) - Jiang, Hua; Nong, Bingjin; Yang, Lijing; Zong, Shaohui; Zhan, Xinli; Wei, Qingjun; Xiao, Zengming
Abstract Background In China, the field of orthopedics has experienced significant growth over the past 12 years. However, the recent status of research on orthopedics among individuals in mainland China, Hong Kong, and Taiwan is unknown. In this study, we investigated characteristics and trends of orthopedics publications from these three regions. Methods Between 2003 and 2014, all articles published in 63 orthopedics journals originating from mainland China, Hong Kong, and Taiwan were identified via Science Citation Index Expanded (SCIE) database. A survey was conducted to systematically analyze the published orthopedics articles from the three regions according to the numbers of articles, study design, impact factors (IFs), citations, most prolific authors, and institutions. Additionally, we evaluated global trends in orthopedics publications, and ranked top 10 countries in terms of the total number of published articles over 12 years and the number of published articles per year. Results A total number of 123, 317 articles were published in the 63 orthopedics journals between 2003 and 2014. The worldwide number of annually published orthopedics articles tended to increase during the study period. The total number of orthopedics publications from the three regions, especially in mainland China, increased markedly from 2003 to 2014. The annual number of orthopedics articles from mainland China increased from 6 in 2003 to 813 in 2014, Hong Kong increased from 32 in 2003 to 71 in 2014, and Taiwan increased from 68 in 2003 to 168 in 2014. For accumulated IFs and total citations of articles, mainland China ranked the first place, followed by Taiwan and Hong Kong. However, publications from Taiwan had the highest average citations per article, and publications from Hong Kong had the highest average IFs. Among the top 10 most prolific authors and institutions, 4 authors and 4 institutions were from Taiwan, 3 authors and 4 institutions were from mainland China, and 3 authors and 2 institutions were from Hong Kong. Conclusions The quantity of articles published in international orthopedics journals from mainland China presented a remarkable upward trend during the past 12 years. Given the relative size of the populations, it should be emphasized that mainland China still has a long way to go to achieve the academic performance of Hong Kong and Taiwan.